2α-Hydroxyalantolactone from Pulicaria undulata: activity against multidrug-resistant tumor cells and modes of action - Hegazy, Mohamed-Elamir F.; Dawood, Mona; Mahmoud, Nuha; Elbadawi, Mohamed; Sugimoto, Yoshikazu; Klauck, Sabine; Mohamed, Nagla; Efferth, Thomas (Phytomedicine, 2021)
Background - Sesquiterpene lactones having α-methylene-γ-lactone moiety are promising natural metabolites showing various biological activity. One of the major metabolites isolated from Pulicaria undulata, 2α-hydroxyalantolactone (PU-1), has not been investigated in detail yet. Multidrug resistance (MDR) represents a major obstacle for cancer chemotherapy and the capability of novel natural products to overcoming MDR is of great interest. - Purpose - Exploring the molecular modes of action for potent natural product metabolites. - Methods - The resazurin reduction assay was employed to evaluate the cytotoxicity of PU-1 on sensitive and their corresponding drug-resistant cell lines (overexpressing P-glycoprotein, BCRP, ABCB5, ΔEGFR, or TP53 knockout). Gene expression profiling was performed by transcriptome-wide mRNA microarray in the human CCRF-CEM leukemic cells after treatment with PU-1. The top significantly up- or down-regulated genes were identified by Chipster program and analyzed using Ingenuity Pathway Analysis (IPA) software. Finally, flow cytometry and Western blotting were performed for cell cycle analyses and apoptosis detection. - Results - The sesquiterpene lactone, PU-1, showed potent cytotoxicity towards the drug-sensitive and -resistant cell lines. Transcriptome-wide mRNA expression profiling and pathway analysis pointed to genes involved in DNA damage response and G2/M cell cycle arrest. G2/M arrest was verified by flow cytometry and further confirmed by the upregulation of p21 and downregulation of p-CDC25C expression in Western blotting. Moreover, the suggested DNA damage checkpoint regulation was confirmed by immunofluorescence and Western blotting by upregulation of pS345 Chk1, p-H3 and γ-H2AX. Furthermore, PU-1 inhibited PI3K/AKT pathway, which is involved in signaling DNA damage and G2/M arrest. Cells ultimately induced apoptosis upon PU-1 treatment. - Conclusions - PU-1 is a potent natural product inhibiting otherwise drug-resistant human tumor cell growth through DNA damage, G2/M cell cycle arrest and apoptosis.
Online Publikationsdatum: 17 November 2020
Gesehen am 18.04.2022